Development and characterization of EST‐SSR markers for the genus Rhododendron section Brachycalyx (Ericaceae). Issue 4 (28th December 2016) - Yoichi, Watanabe; Sakaguchi, Shota; Ueno, Saneyoshi; Tomaru, Nobuhiro; Uehara, Koichi
Abstract : Simple sequence repeat (SSR) markers were developed from expressed sequence tags (ESTs) for Rhododendron section Brachycalyx in order to elucidate its evolutionary processes and reproductive ecology. Nineteen polymorphic EST‐SSR markers were developed from EST libraries of R. amagianum and R. hyugaense . Polymorphisms for these markers were assessed using four species of section Brachycalyx . The number of alleles ranged from 1 to 14, and the observed and expected heterozygosity ranged from 0.000 to 0.931 and 0.000 to 0.904, respectively. The EST‐SSR markers developed in this study will be useful for elucidating population genetic structure and breeding systems in section Brachycalyx . Abstract : We developed 19 EST‐SSR markers for Rhododendron section Brachycalyx . The EST‐SSR markers developed in this study will be useful for elucidating population genetic structure and breeding systems in section Brachycalyx .